Comparing bond strength and marginal integrity with direct bulk-fill resin composites and indirect composites - Barros, Yolanda; Bandéca, Mateus; Millán, Andrés; Siqueira, Fabiana; Kuga, Milton [UNESP]; Fernandez, Eduardo; Chaple Gil, Alain Manuel; Borges, Alvaro; Tonetto, Mateus (My University, 2019)
Introduction: The clinical longevity of tooth restoration -whether directly or indirectly using composites- greatly depends on the quality and stability of the marginal adaptation. Even today, dental restoration failure is a major complication in everyday dental practice. Objective: To evaluate the effect of restoration techniques on the microtensile bond strength and marginal integrity of class II cavities. Methods: An experimental in vitro investigation was made. Preparations (5 × 4 × 2 mm) below the cement-enamel junction were performed in 45 human maxillary premolars (n= 15) that were the sample of the study selected to random. The G1 group incrementally received Spectrum TPH3 Dentsply De trey in three horizontal incremental layers. The G2 group received a bulk restoration technique (one 4-mm increment of Surefill SDR flow plus one 1-mm horizontal capping layer of Spectrum TPH3 Dentsply De trey using a metal matrix band. For the G3 group, impressions were made from each cavity preparation, and Spectrum was used to complete an indirect composite restoration. After storage (24 h/37 °C), the proximal surfaces of each tooth were polished with Sof-Lex disks. For microtensile bond strength testing, all premolars were sectioned into resin-dentine beams (0.8 mm2) and were tested under tension (0.5 mm/min). Results: Microtensile bond strength testing and marginal integrity values were not statistically significantly affected by the type of restoration technique used (p> 0.05). Conclusions: The SurefillSDR flow that used a capping layer made of conventional composite can be an alternative to reduce procedure durations as well as additional steps in the restorative technique.
Comparación de la fuerza de unión y la integridad marginal con compuestos de resina de relleno masivo y compuestos indirectos
Keywords: Bond strength; Fiber post; Resin cement